FINANCIAL STRATEGY IMPLEMENTATION FOR BUSINESS PLAN AT MATERIAL HANDLING RENTAL SERVICES STARTUP LOGISME - Chitra Mukti; Rhian Indradewa; Edi Hamdi; Ketut Sunaryanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
A new business consists with risk, As a material handling startup business in material handling rental, The Companies need quite a large amount of capital, in the Government Regulation (PP) of the Republic of Indonesia No. 7 of 2021 it is stated in article 35 that medium-sized businesses are any company that has a business capital of between 5 and 10 billion. The financial goal is to maintain operational cash flow used effectively and efficiently so that the company's vision can be achieved. LogisMe planning for the smart goals and aim for financial planning, then planning the company’s expense and income, therefore LogisMe can generates for the simulation of balance sheet, income statement, cash flow, etc. Next the investor can due diligence with analysis of the result of mix match analysis for investation ratios e.g. ARR, ROI, NPV, PP and IRR, as the result the liqudity, solvability and profitability ratios will be reported. The financial projection reflects in the both income statement, cash flow and balance sheet. Meanwhile In investment feasibility analysis, there are several important elements, namely NPV used to calculate the value of the forecast cash flow, IRR for business return rating analysis and Payback Period for analysis of the duration of initial investment returns.